Phenotypic, morphological, and metabolic characterization of vascular‐spheres from human vascular mesenchymal stem cells. Issue 2 (27th August 2021) - Valente, Sabrina; Ciavarella, Carmen; Hernández‐Aguilera, Anna; Salvador, Fernández‐Arroyo; Buzzi, Marina; Joven, Jorge; Pasquinelli, Gianandrea
Abstract: The ability to form spheroids under non‐adherent conditions is a well‐known property of human mesenchymal stem cells (hMSCs), in addition to stemness and multilineage differentiation features. In the present study, we tested the ability of hMSCs isolated from the vascular wall (hVW‐MSCs) to grow as spheres, and provide a characterization of this 3D model. hVW‐MSCs were isolated from femoral arteries through enzymatic digestion. Spheres were obtained using ultra‐low attachment and hanging drop methods. Immunophenotype and pluripotent genes (SOX‐2, OCT‐4, NANOG) were analyzed by immunocytochemistry and real‐time PCR, respectively. Spheres histological and ultrastructural architecture were examined. Cell viability and proliferative capacity were measured using LIVE/DEATH assay and ki‐67 proliferation marker. Metabolomic profile was obtained with liquid chromatography–mass spectrometry. In 2D, hVW‐MSCs were spindle‐shaped, expressed mesenchymal antigens, and displayed mesengenic potential. 3D cultures of hVW‐MSCs were CD44 +, CD105 low, CD90 low, exhibited a low propensity to enter the cell cycle as indicated by low percentage of ki‐67 expression and accumulated intermediate metabolites pointing to slowed metabolism. The 3D model of hVW‐MSCs exhibits stemness, dormancy and slow metabolism, typically observed in stem cell niches. This culture strategy can represent an accurate model to investigate hMSCs features for future clinical applications in the vascular field. Abstract : hVW‐MSCs are able to form spheres, characterized by high NANOG and CD44 expression, low ki‐67 levels and slow metabolism. hVW‐MSC spheres represent an in vitro model of stem cell niche, suitable for investigating MSCs in the vascular field.